2018
DOI: 10.3847/1538-4357/aae8e1
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and Rings in an ALMA Survey of Disks in the Taurus Star-forming Region

Abstract: Rings are the most frequently revealed substructure in ALMA dust observations of protoplanetary disks, but their origin is still hotly debated. In this paper, we identify dust substructures in 12 disks and measure their properties to investigate how they form. This subsample of disks is selected from a high-resolution (∼ 0.12 ) ALMA 1.33 mm survey of 32 disks in the Taurus star-forming region, which was designed to cover a wide range of sub-mm brightness and to be unbiased to previously known substructures. Wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
552
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 528 publications
(622 citation statements)
references
References 108 publications
32
552
4
Order By: Relevance
“…(ii) Planet formation simulations are missing some important ingredients regarding gas accretion (see also Nayakshin et al (2019)) and planet migration. The survey by Long et al (2018) in the Taurus star-forming region and the survey by Cieza et al (2019) in the Ophiuchus starforming region, on the other hand, found a significant population of very compact discs (outer disc radii ¡ 30 au). These discs are not pictured within the DSHARP sample, due to the selection biases in the DSHARP campaign (Andrews et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…(ii) Planet formation simulations are missing some important ingredients regarding gas accretion (see also Nayakshin et al (2019)) and planet migration. The survey by Long et al (2018) in the Taurus star-forming region and the survey by Cieza et al (2019) in the Ophiuchus starforming region, on the other hand, found a significant population of very compact discs (outer disc radii ¡ 30 au). These discs are not pictured within the DSHARP sample, due to the selection biases in the DSHARP campaign (Andrews et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Tidal interaction can be effective in removing dust mass from a disk even in later stages when the disk is in a binary system (e.g. Artymowicz & Lubow 1994), as proposed to explain the low mm flux of some objects in Taurus by Long et al (2018). A higher than usual binary fraction could therefore explain the low disk masses observed in CrA.…”
Section: Is Cra Young?mentioning
confidence: 99%
“…The morphological characterization of dust grains in protoplanetary disks is much more advanced than that of molecular species. In fact, high-resolution images at either near-IR or (sub)millimeter wavelengths are currently available for more than a hundred sources (e.g., Garufi et al 2017;Avenhaus et al 2018;Andrews et al 2018;Long et al 2018). The vast majority of these objects are Class II sources (following Lada 1987), namely stars older than ∼1 Myr that are visible at optical wavelengths and show a spectral energy distribution (SED) composed of a stellar blackbody plus a substantial IR excess from the surrounding disk.…”
Section: Introductionmentioning
confidence: 99%